RETROPERITONEAL CYSTIC LYMPHANGIOMA: CASE REPORT OF A RARE ENTITY - Vieira, Isabel (2021)
Cystic lymphangioma is a rare and benign malformation of the lymphatic system, with retroperitoneal location accounting for only 1% of all lymphangiomas. Clinical presentation is frequently nonspecific. Authors present a case report of a 38 years old woman with persistent abdominal pain refractory to treatment that required imaging investigation (abdominal ultrasound and thoraco-abdominopelvic computed tomography scan) unveiling a cystic retroperitoneal mass suggesting lymphangioma. Abdominal laparotomy was performed for complete excision of the tumor. Histopathological exam of surgical specimen confirmed the cystic lymphangioma diagnosis. Complete surgical excision is considered gold-standard therapy and allow definite diagnosis.